Workability Of The Norms Of Transparency And Accountability Against Corruption In Nigeria - Igbinedion, Simeon (Journal of Sustainable Development Law and Policy, 2025)
This paper discusses the workability of the existing norms of transparency and accountability in the battle against corruption in Nigeria. Incontrovertibly, high level corruption pervades every nook and cranny of the country to the detriment of its citizens. Although anti-corruption norms exist in the Nigerian legal order, high profile corruption remains endemic, suggesting that the norms are unworkable. This paper argues that the unworkability of transparency and accountability norms in Nigeria is largely attributable to the contradictions, inconsistencies or deficiencies inherent therein. Consequently, the paper suggests ways of putting the norms to work against corruption in Nigeria.